2014
DOI: 10.1080/17461391.2014.940560
|View full text |Cite
|
Sign up to set email alerts
|

Brachial artery characteristics and micro‐vascular filtration capacity in rock climbers

Abstract: Rock climbers perform repeated isometric forearm muscle contractions subjecting the vasculature to repeated ischaemia and distorted haemodynamic signals. This study investigated forearm vascular characteristics in rock climbers compared to healthy untrained controls. Eight climbers (CLIMB) (BMI; 22.3, s = 2.0 kg/m 2 , isometric handgrip strength; 46, s = 8 kg) were compared against eight untrained controls (CON) (BMI; 23.8, s = 2.6 kg/m 2 , isometric handgrip strength; 37, s = 9 kg). Brachial artery diameter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 67 publications
(96 reference statements)
0
20
0
Order By: Relevance
“…These results demonstrate that rock climbers have increased vasculature which provides information that repeated isometric ischemic conditions enhance vascular adaptations 19 . The results of our study show a 4.5% increase in forearm girth in the dominant hand and a 4.4% increase in forearm girth in the non-dominant hand.…”
Section: Rest Periodmentioning
confidence: 67%
See 1 more Smart Citation
“…These results demonstrate that rock climbers have increased vasculature which provides information that repeated isometric ischemic conditions enhance vascular adaptations 19 . The results of our study show a 4.5% increase in forearm girth in the dominant hand and a 4.4% increase in forearm girth in the non-dominant hand.…”
Section: Rest Periodmentioning
confidence: 67%
“…Cold water immersion is a technique that is believed to induce localized vasoconstriction which reduces acute inflammation in the forearms 18 . Previously, vascular characteristics of rock climbers have been compared to untrained individuals, where brachial artery diameter and blood flow were measured 19 . It was hypothesized that rock climbers would show enlarged artery diameter and enhanced capillary filtration and capillary density 20 .…”
Section: Rest Periodmentioning
confidence: 99%
“…As such climbing ability on short bouldering routes may not be associated with the amount of re-oxygenation, but rather the type of climbing that the climbers predominantly took part in. It has been previously shown that in sport climbers, local vascular adaptations represent a higher reactive hyperaemic blood flow and capillary filtration capacity of forearm muscles (Thompson, Farrow, Hunt, Lewis, & Ferguson, 2014). These adaptations are due to the oxygen demands of the activity (sport climbing) generally lasting between two to seven minutes (Watts, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…According to these results, it is suggested that these differences are due to climbing discpline-specific finger flexor adaptations. Previous research (Fryer, Stoner, Scarrott et al, 2015) has suggested that there are no differences in the macrovascular structure of the finger flexors between ability groups, although microvascular adaptions have been reported (Thompson, Farrow, Hunt, Lewis & Ferguson, 2014). Moreover, experienced climbers have been shown to be able to deoxygenate the FDP to a greater extent than their lower grade counterparts (Fryer et al, 2014;Fryer, Stoner, Scarrott et al, 2015;.…”
Section: Discussionmentioning
confidence: 99%